A study on the possibility to use Raspberry Pi as a console server for remote access to devices in virtual learning environments - Kyuchukova, Diyana; Hristov, Georgi; Zahariev, Plamen; Borisov, Svilen (2015 International Conference on Information Technology Based Higher Education and Training (ITHET), 2015)
During the last years many virtual laboratories have been developed, but not all of them were successfully adopted. Designing, planning and creating a virtual laboratory can be a very difficult process, which can get even more complicated if the laboratory has to provide access to real equipment. One of the most problematic steps when developing such virtual laboratories is the selection of the right access method. At the present moment of time there are many technologies that allow users to access devices remotely. One of these possible solutions is to use the Telnet/SSH protocols for remote access. Nevertheless, the use of these protocols require at least one active network interface per device, which in some cases can present a problem. There are some other drawbacks of using Telnet/SSH for remote access as well - virtual laboratories are often created with the purpose to be used in the education process, which means that the users of these systems in most cases are students. These less experienced users might accidently delete the configuration of the interface that is dedicated for the remote access, which will result in the immediate loss of connection to the device and will require administrator intervention to fix this access issue. An alternative solution to provide remote access is to use a console server. A detailed analysis on the possibilities for remote access using console servers, present them as reliable, but also as a very expensive solutions. In this paper we will investigate the possibilities to replace the expensive console servers with much cheaper devices. One such device is the Raspberry Pi - a low cost device that was developed to enhance the education process of children and students in the field of the computer sciences and their related subjects. In this paper we will investigate and compare the characteristics of the Raspberry Pi to the most widely used console servers and we will present a way to use the Raspberry Pi as a console server for remote access to telecommunication routers and switches.